If you're in a dogfight, become a cat! : strategies for long-term growth - Sherman, Len, 1956- (Columbia University Press, 2017)
Businesses often find themselves trapped in a competitive dogfight, scratching and clawing for market share with products consumers view as largely undifferentiated. Conventional wisdom suggests that dogfights are to be expected as marketplaces mature, giving rise to the notion that there are "bad" industries where it is unlikely that any company can succeed. But there are notable exceptions in which enlightened executives have changed the rules to grasp the holy grail of business: long-term profitable growth